Wnt-signaling enhances neural crest migration of melanoma cells and induces an invasive phenotype - Tobias Sinnberg (Molecular Cancer, 2018)
Abstract Background During embryonic development Wnt family members and bone morphogenetic proteins (BMPs) cooperatively induce epithelial-mesenchymal transition (EMT) in the neural crest. Wnt and BMPs are reactivated during malignant transformation in melanoma. We previously demonstrated that the BMP-antagonist noggin blocked the EMT phenotype of melanoma cells in the neural crest and malignant invasion of melanoma cells in the chick embryo; vice-versa, malignant invasion was induced in human melanocytes in vivo by pre-treatment with BMP-2. Results Although there are conflicting results in the literature about the role of β-catenin for invasion of melanoma cells, we found Wnt/β-catenin signaling to be analogously important for the EMT-like phenotype of human metastatic melanoma cells in the neural crest and during invasion: β-catenin was frequently expressed at the invasive front of human primary melanomas and Wnt3a expression was inversely correlated with survival of melanoma patients. Accordingly, cytoplasmic β-catenin levels were increased during invasion of melanoma cells in the rhombencephalon of the chick embryo. Fibroblast derived Wnt3a reduced melanoma cell adhesion and enhanced migration, while the β-catenin inhibitor PKF115–584 increased adhesion and reduced migration in vitro and in the chick embryonic neural crest environment in vivo. Similarly, knockdown of β-catenin impaired intradermal melanoma cell invasion and PKF115–584 efficiently reduced liver metastasis in a chick chorioallantoic membrane model. Our observations were accompanied by specific alterations in gene expression which are linked to overall survival of melanoma patients. Conclusion We present a novel role for Wnt-signaling in neural crest like melanoma cell invasion and metastasis, stressing the crucial role of embryonic EMT-inducing neural crest signaling for the spreading of malignant melanoma.